A revised experimental method of integrating sustainability into the undergraduate design studio. (21st May 2021) - Mohamed, Kamal Eldin
Architecture education predestines students for their careers by teaching them design skills and technical knowledge. The design is a reiterative decision, which results in strategies of resource use to produce a system to respond to human necessity or find a solution to existing problems. Building sustainability has been included in many architecture education curricula but there has been a lack of integrating sustainability principles into the design studio. This experimental study presents an improved design studio method with restructured teaching tools of the first experimental study of sustainable architectural design studio (SADS). Additionally, it illustrates the studio outcome as well as presents the evaluation and assessment of the experimental. Moreover, it introduces the research finding along with the recommendation for future design studio experimental.